The biventricular dysfunction evaluation in the different types of pulmonary hypertension. (14th October 2021) - Sirenko, Y; Zhyvilo, I; Radchenko, G; Torbas, O; Batsak, Y
Abstract: Background: Right ventricular (RV) function is well-known prognostic factor in patients with pulmonary hypertension (PH). However, situation becomes critical when underfilling of left ventricle (LV) leads to systemic hypoperfusion and scenario worsening. Objective: To evaluate the relationship of RV and LV dysfunction in patients with the different forms of PH. Methods: We evaluated parameters of RV and LV function and their relationship during right heart catheterization (RHC) in 125 patients with different forms of pulmonary arterial hypertension (PAH) and 51 patients with chronic thromboembolic PH (CTEPH), 7 patients with PH associated with left heart disease (LHD) and 17 patients in whom PH was excluded after procedure. In all patients recommended echocardiography protocol (Echo) and NT-proBNP level evaluation were performed. Results: In the group without PH the RV stroke work index (RVSWI) level and its ratio to the LV stroke work index (LVSWI) were lowest and in the normal range: 7, 0±0, 7 ml·mmHg/m 2 and 0, 13±0, 02 respectively. In all patients with PH, we noted the significant elevation of RVSWI >20 ml·mmHg/m 2 . Patients with PAH and CTEPH had a smaller left atrium, LV volumes on Echo and decreased stroke volume and pulmonary artery wedge pressure. The underfilling of LV in IPAH and CTEPH groups accompanied by severe lowering of LWSWI to 35–45 ml·mmHg/m 2 (p<0, 05 compared with LHD group and patients without PH). In spite of the levels of cardiac index were similar in patients with LHD and without PH, the RVSWI (23, 1±2, 7 ml·mmHg/m 2 ) and its RVSWI/LVSWI ratio (0, 53±0, 09) were significantly higher in LHD group and confirmed severe RV overload. Only in HIV infection group observed severe depression of the pumping function of both heart's sides and levels of RWSWI and LVSWI were lowest, but the ratio was elevated (0, 53) and indicated RV overload. Similar data were observed when we compare pumping coefficients of RV and LV in different groups. We did not find any association between NT-proBNP level and the LV volume and function. Conclusion: The simultaneous evaluation of parameters of RV and LV function and their ratio during RHC in patients with different types of PH allowed not just to estimate the degree of RV overload and dysfunction, but also LV underfilling and dysfunction. FUNDunding Acknowledgement: Type of funding sources: None.